Performance evaluation of single cylinder two-stroke engine equipped with direct injection system using GT POWER software [electronic resource] - 217211 Muhammad Khairul Azmir Ab. Hamid (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2006